Atmospheric pressure floating electrode-dielectric barrier discharges (FE-DBDs) having flexible electrodes - Kim, Jun Hyun; Park, Chang Jin; Kim, Chang Koo (Korean Chemical Engineering Research, 2019)
An atmospheric pressure floating electrode-dielectric barrier discharge (FE-DBD) system having flexible electrodes was developed and its plasma characteristics was investigated. Polytetrafluoroethylene (PTFE), polydiemethylsiloxane (PDMS), and polyethylene terephthalate (PET) were used as flexible dielectrics for flexible powered-electrodes. The optical intensity and electron temperature of the atmospheric pressure FE-DBD plasma increased with the voltage applied to the powered electrode, and increased in the order of PTFE < PDMS < PET at a fixed voltage. This behavior was explained in terms of the change in the capacitance of the flexible dielectrics with the dielectric type and voltage, implying that the plasma characteristics of an atmospheric pressure FE-DBD having flexible electrodes can be controlled by modulating the flexible dielectrics for the flexible powered-electrode and the voltage applied to the powered electrode. Because an atmospheric pressure FE-DBD system can generate a plasma along the curvature of skins, it is expected to have useful applications in plasma medicine.
Keywords: Atmospheric pressure floating electrode-dielectric barrier discharge; Dielectrics; Flexible electrode; Plasma; Plasma medicine